Short-range ordering and its effects on mechanical properties of high-entropy alloys. (30th January 2021) - Wu, Yuan; Zhang, Fei; Yuan, Xiaoyuan; Huang, Hailong; Wen, Xiaocan; Wang, Yihan; Zhang, Mengyuan; Wu, Honghui; Liu, Xiongjun; Wang, Hui; Jiang, Suihe; Lu, Zhaoping
Abstract: In this letter, we briefly summarize experimental and theoretical findings of formation and characterization of short-range orderings (SROs) as well as their effects on the deformation behavior of high-entropy alloys (HEAs). We show that existence of SROs is a common yet key structural feature of HEAs, and tuning the degree of SROs is an effective way for optimizing mechanical properties of HEAs. In additional, the challenges concerning about formation mechanism and characterization of SROs in HEAs are discussed, and future research activities in this regard are also proposed.